X-Ray Structure Analysis of Nardin - Nayak, A.; Dutta, U.; A. Chatterjee, (Late); Banerji, J.; Prange, T. (Asian Journal of Chemistry, 2010)
Structural determination of nardin, a novel sesquiterpene acid, is reported. The crystal structure of this compound is determined by single crystal X-ray studies. X-ray crystallography revealed the presence of two conformers arising from the intermolecular hydrogen bond of the O–H···O type. The crystal of the compound belongs to the tetragonal crystal system and space group is P41212 (or P43212). Crystal data are as follows: a = 11.030 (3) Å, b = 11.030 (3) Å, c = 43.350 (5) Å; V = 5274 Å3; Z = 16. The final R factors are R = 0.065 (for all 2399 accepted reflections), R = 0.064 (for 2355 observed reflections).